PENERAPAN LOGIKA FUZZY PADA PENILAIAN MUTU TEH HITAM ORTHODOX - Roni Kastaman; Sudaryanto Zain; Sigit B. Prayudo (PERTETA, 2007)
ABSTRACT In testing quality process of the orthodox black tea by using tea organoleptic expert, there is often found a problem of tester sensoric restriction. Based on this conditon the research has been carried out by using fuzzy modelling technique, which aimed to explore ruther more about how fuzzy method can concordance with fuzzy range value on black olthodox tea assesment. So that, it could be more objective on quality evalualion. The research has beld on May to June 2005 in tea plantation facility of PTPN Vlll Malabar. Pangalengan, and Tea and Cinchona Research Center (Pusat Penelitian Ten dan Kina -PPTK) Gembung, Cieidey, West Java. This fuzzy method can keep a record experience of the orthodox black tea tester and also correct the result of the determination done by the tester, Based on the parametrik LSD test and non-parametrik Mann-Whitney, there is no significant value diference In the result of the determination done by the tester and by using the fuzzy logic. So that the fuzzy logic method can be used as a method in orthodox black tea quality determination. But The method can not be used if there is a far diference in the tea determination between one tester to the others. Tbe best defuzzification method for tea quality detemination in this occasion is Smallest of Maximum (SOM) method.Keyword: Fuzzy Logic, Orthodox Black Tea, Quality Determination. Diterima: 30 Juli 2007; Disetujui: 22 Agustus 2007